PENGARUH PEMAHAMAN SISTEM AKUNTANSI, PENGENDALIAN INTERN TERHADAP PENYERAPAN ANGGARAN DENGAN PENGELOLAAN KEUANGAN DAERAH SEBAGAI VARIABEL INTERVENING DI PEMERINTAH PROVINSI JAWA TENGAH - Susi Dwi Haryanti, 1342020014 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The achieving aim of this research is to analize the influence of accountancy system and intern controlling toward district finances management in central java goverment. To analize the influence of accountancy sistem comprehension, intern controlling and district finances management toward district finances estimate absorbtion in central java goverment. Population in this research is 124 of employees or finances staffs at 50 SKPD in central java goverment. The sampling technic in this research is using purpose sampling. Therefor obtained 118 sampling of employees or finances staffs. Data collecting methodeis using questioner and data analising is using linier regresionanalising. Based on the data analize, the conclusion can be got is partially (individually) accountancy system comprehension gives positive influence and significant toward district finances management. Partially (individually) intern controlling givespositive influences and significant toward the district finances management. Partially (individually) accountancy system comprehension gives positive influence and significant toward estimate absorbtion. Partially (individually) intern controlling gives positive influence and significant toward estimatreabsorbtion. Partially (individually) district finances management gives positive influence and significant toward estimate absorbtion. District finances management does not intervening accountancy system comprehension toward estimate absorbtion. District finances management does not intervening intern controlling toward estimateÂ  absorbtion. Keyword : Understanding of accounting system, internal control, monetary management of and area absorbtion of budget